Climate Change Adaptation in Nepal: Exploring Ways to Overcome the Barriers - Regmi, Bimal Raj; Bhandari, Dinanath (Journal of Forest and Livelihood, 2013)
DOI: http://dx.doi.org/10.3126/jfl.v11i1.8612 Journal of Forestry and Livelihood Vol.11(1) 2013 43-61